2003
DOI: 10.21273/hortsci.38.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Nitrogen Status in Pansy

Abstract: Two experiments were conducted with pansy (Viola ×wittrockiana Gams `Bingo Yello') to determine the relationship between foliar nitrogen (% of dry weight) (FN) and either sap nitrate concentration (SN) in petioles or SPAD readings of foliage. FN was highly correlated to SN throughout both experiments (r = 0.80 to 0.91). FN was poorly correlated to SPAD readings early in both experiments (r = 0.54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…All sensor readings increased as N rates increased over time, which corresponds with similar findings in other ornamental crops like begonia, dianthus, geranium, marigold, poinsettia, and zinnia (Altland et al, 2002;Khan et al, 2004;Schuch et al, 1996;Smith et al, 2004;Wang et al, 2012a,b). All sensors showed quadratic responses across treatments over time due to experiment length primarily (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…All sensor readings increased as N rates increased over time, which corresponds with similar findings in other ornamental crops like begonia, dianthus, geranium, marigold, poinsettia, and zinnia (Altland et al, 2002;Khan et al, 2004;Schuch et al, 1996;Smith et al, 2004;Wang et al, 2012a,b). All sensors showed quadratic responses across treatments over time due to experiment length primarily (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The plants grown in 100% SMW or in media without NPK amendment suffered from nitrogen deficiency resulting in leaf chlorosis and low SPAD values. Altland et al [40] also confirmed that leaf chlorophyll content is often correlated with the nitrogen content of growth media. Our findings are also supported by a study performed by Altland and Krause [41] in which they observed the differences in SPAD values among growth media.…”
Section: Discussionmentioning
confidence: 91%
“…Several authors found that Cardy meter analysis of fresh plant sap was well correlated with several methods of dry tissue extract and analysis for NO 3 -N and suggested the Cardy could provide rapid, precise NO 3 -N measurements for a variety of crops (Altland et al, 2002(Altland et al, , 2003Hartz et al, 1993;Kubota et al, 1996;Rosen et al, 1996;Westcott et al, 1993Westcott et al, , 1998. Authors note that it may be necessary to dilute samples that are beyond the calibration range of the meter (Hochmuth, 1994;Rosen et al, 1996;Westcott et al, 1993), although Rosen et al (1996) found a linear relationship between methods of analysis up to 2000 mgÁL -1 NO 3 -N, suggesting that the linear range of the Cardy meter extends well beyond the high standard concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Relatively inexpensive and portable ISE nutrient monitoring devices such as the Cardy NO 3 -N meter (Horiba Insruments, Irvine, CA, and Spectrum Technologies, Plainfield, IL) are capable of measuring fresh plant sap NO 3 -N levels directly. Several authors have shown that measurements made with the Cardy meter using nondiluted plant sap were well correlated to conventional methods of NO 3 -N analysis (Altland et al, 2002(Altland et al, , 2003Hartz et al, 1993;Westcott et al, 1998). However, others found Cardy meter NO 3 -N values were consistently higher than values derived from conventional analysis methods unless sap was diluted to account for ionic strength effects and specific ion interferences (Davenport and Jabro, 2001;Errebhi et al, 1998;Hochmuth, 1994;Kubota et al, 1996;Rosen et al, 1996;Westcott et al, 1993).…”
mentioning
confidence: 99%